FRASA DALAM BAHASA ARAB (Konstruksi Frasa Dalam Bahasa Arab Berdasarkan Unsur Kata Pembentuknya) - Asna Andriani (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2016)
Language is a means of social communication in society. We can think and communicate our thoughts with language. Similarly science, culture, and civilization was basically learned and passed from generation by using the language. Without language the interaction and communication between humans is very limited. Likewise Arabic as a foreign language in Indonesia occupies a strategic position, especially for Muslims. It is not only the Arabic language used in religious rituals, but also became the language of science and the language of international relations. Arabic has the rules in respect of preparation of speech, ranging from words, phrases, clauses, and sentences. One branch of linguistic study that discusses the rules above is syntactically (Sharf), which addressed the issue of linguistic capitalize the word. While a construction smallest capitalize the word is the phrase. Furthermore, this paper will explain the construction of phrases in Arabic by the word constituent element, which is expected to facilitate the preparation of the phrase is true and can give understanding.